ANALISIS PENGARUH BUDAYA ORGANISASI DAN KOMPENSASI TERHADAP KINERJA KARYAWAN DENGAN MOTIVASI SEBAGAI VARIABEL INTERVENING (Studi Kasus pada PT. LG Bagian Penjualan Indonesia Semarang) - Alexander Monte Christo Arta Graha; Edy Rahardja (Faculty of Economics and Business Diponegoro University, 2016)
The problems that occurred in the employee portion of sales LG Indonesia Semarang is adecline in performance is indicated by not achieving the target for 2015. The employeeperformance and motivation is also thought to be influenced by factors of organizationalculture and also compensation deemed not feasible by most employees. This study aimedto analyze the influence of organizational culture on the motivation and compensationand employee performance parts sales LG Indonesia Semarang. The population used inthis study were all employees of LG Indonesia Semarang. The sampling technique usedwas purposive sampling. Criteria samples taken were all employees of the salesdepartment LG Indonesia Semarang who have worked more than two years are 71nurses. The method of collecting the data in this study using questionnaires andinterviews. Methods of data analysis using path analysis. Based on the research,organizational culture and compensation have a positive effect on motivation andperformance, while motivation is also a positive effect on performance. Based on theresults Sobel Test to determine whether there is mediating the relationship between theindependent and dependent variables, it is known that motivation mediates the effect ofcompensation and organizational culture on performance.